VD_FINDINFO HC / 2012 / 611 vom 18. September 2012 - VD Tribunal cantonal (2012)
LOYER, DEMEURE DU DÉBITEUR, RÉSILIATION IMMÉDIATE, PROCÉDURE SOMMAIRE | 257 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 317 al. 1 CPC (CH)